Contribution of Rare Genetic Variation to Disease Susceptibility in a Large Scandinavian Myositis Cohort. Issue 2 (23rd December 2021) - Bianchi, Matteo; Kozyrev, Sergey V.; Notarnicola, Antonella; Hultin Rosenberg, Lina; Karlsson, Åsa; Pucholt, Pascal; Rothwell, Simon; Alexsson, Andrei; Sandling, Johanna K.; Andersson, Helena; Cooper, Robert G.; Padyukov, Leonid; et al.
Abstract : Objective: Idiopathic inflammatory myopathies (IIMs) are a heterogeneous group of complex autoimmune conditions characterized by inflammation in skeletal muscle and extramuscular compartments, and interferon (IFN) system activation. We undertook this study to examine the contribution of genetic variation to disease susceptibility and to identify novel avenues for research in IIMs. Methods: Targeted DNA sequencing was used to mine coding and potentially regulatory single nucleotide variants from 1, 900 immune‐related genes in a Scandinavian case–control cohort of 454 IIM patients and 1, 024 healthy controls. Gene‐based aggregate testing, together with rare variant– and gene‐level enrichment analyses, was implemented to explore genotype–phenotype relations. Results: Gene‐based aggregate tests of all variants, including rare variants, identified IFI35 as a potential genetic risk locus for IIMs, suggesting a genetic signature of type I IFN pathway activation. Functional annotation of the IFI35 locus highlighted a regulatory network linked to the skeletal muscle–specific gene PTGES3L, as a potential candidate for IIM pathogenesis. Aggregate genetic associations with AGER and PSMB8 in the major histocompatibility complex locus were detected in the antisynthetase syndrome subgroup, which also showed a less marked genetic signature of the type I IFN pathway. Enrichment analyses indicated a burden of synonymous and noncoding rare variants in IIM patients, suggesting increased disease predisposition associated with these classes of rare variants. Conclusion: Our study suggests the contribution of rare genetic variation to disease susceptibility in IIM and specific patient subgroups, and pinpoints genetic associations consistent with previous findings by gene expression profiling. These features highlight genetic profiles that are potentially relevant to disease pathogenesis.